Pan‐cancer analysis identifies CD300 molecules as potential immune regulators and promising therapeutic targets in acute myeloid leukemia - Zi‐jun Xu; Ye Jin; Xin‐long Zhang; Pei‐hui Xia; Xiang‐mei Wen; Ji‐chun Ma; Jiang Lin; Jun Qian (Cancer Medicine, 2023)
Abstract Background CD300s are a group of proteins playing vital roles in immune responses. However, much is yet to be elucidated regarding the expression patterns and clinical significances of CD300s in cancers. Methods In this study, we comprehensively investigated CD300s in a pan‐cancer manner using multi‐omic data from The Cancer Genome Atlas. We also studied the relationship between CD300s and the immune landscape of AML. Results We found that CD300A‐CD300LF were generally overexpressed in tumors (especially AML), whereas CD300LG was more often downregulated. In AML, transactivation of CD300A was not mediated by genetic alterations but by histone modification. Survival analyses revealed that high CD300A‐CD300LF expression predicted poor outcome in AML patients; the prognostic value of CD300A was validated in seven independent datasets and a meta dataset including 1115 AML patients. Furthermore, we demonstrated that CD300A expression could add prognostic value in refining existing risk models in AML. Importantly, CD300A‐CD300LF expression was closely associated with T‐cell dysfunction score and could predict response to AML immunotherapy. Also, CD300A was found to be positively associated with HLA genes and critical immune checkpoints in AML, such as VISTA, CD86, CD200R1, Tim‐3, and the LILRB family genes. Conclusions Our study demonstrated CD300s as potential prognostic biomarker and an ideal immunotherapy target in AML, which warrants future functional and clinical studies.